Pathophysiology of Transmissible Spongiform Encephalopathies - Scallet, A.C.; Carp, R.I.; Ye, X. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2003)
Transmissible spongiform encephalopathies (TSEs) are an intriguing group of diseases that are a challenge to rational drug design for treatment or prevention by medicinal chemists and pharmacologists. There are similarities between brain pathological changes caused by excitatory amino acids (EAAs) toxicity and by TSE infection. Neurons mediating the neuroendocrine functions of the hypothalamus as well as Purkinje cells of the cerebellum are targets for damage by TSEs and EAAs. Both EAAs and TSE agents cause astrocytosis. TSEs commonly feature swollen astrocytes either containing abnormal prion proteins (PrPSc) or located immediately adjacent to PrPSc deposits in the neuropil. Antigenic properties of the PrPSc may stimulate the release of nearby microglial and astrocytic cytokines, resulting in dysfunction and damage to elements of the neuropil. Such swollen astrocytes also commonly occur following exposure to a number of other neurotoxicants such as EAAs. Early neuropathological changes in scrapie involve primarily astrocytes and nerve terminals, but not nerve-cell bodies or spongiform changes. These data suggest that the initial events in the pathophysiology of TSEs may be the astrocytic response to PrPSc accumulation, leading to NOS / free radical damage to nearby nerve terminals. We will review the similarities in brain pathological changes caused by TSEs and EAAs. We suggest that the end-stage neuropathology produced by TSEs has many of the characteristics of EAA-mediated neuronal necrosis, a well-established final common pathway of neurodegeneration from a variety of neurotoxicants. The cytoprotective effects of the antagonists of the NMDA receptor-channel complex such as memantine (1-amino-3,5- dimethyladamantane; MEM), MD-ADA (1-N-methylamino-3,5-dimethladamantane) or dizolcipine (MK-801, (+)-5- methyl-10,11-dihydro-5H-dibenzo(a,d)cyclohepten-5,10-imine malate) will be considered.
Keywords: memantine